Cooperative optimization of shore power allocation and berth allocation: A balance between cost and environmental benefit. (10th January 2021) - Peng, Yun; Dong, Meng; Li, Xiangda; Liu, Huakun; Wang, Wenyuan
Abstract: Shore power is the use of shore-side electricity to satisfy ships' electricity demand during berthing at ports. It is an effective measure of reducing the emissions produced by auxiliary engines of ships at berth. This paper develops a cooperative optimization method to model the problem of whether to allocate shore power for each berth and which berth is allocated for the stochastic arriving ship. The cooperative optimization method is to minimize the total cost of installing and using shore power systems and maximize the environmental benefit of reducing air pollution and greenhouse gas emissions. Considering the emission of different pollutants can't be directly accumulated as the objective, different pollutants are uniformly expressed as economic penalties by imposing environmental taxes and then economic penalties are regarded as the objective of environmental benefits. Firstly, the problem is carried out by proposing a multi-objective cooperative optimization model from the perspective that both shipping and port companies take overall benefits of port supply chains as the optimization target. Next, the multi-objective particle swarm optimization algorithm is adopted to resolve the model. Then, a proposed bulk terminal/wharf is taken as an example to conduct experiments for gaining optimal solutions under different carbon pricing policy scenarios. After then, based on the proposed preference-based decision-making method, optimal decisions under different preference are obtained. Finally, in order to analyze the applicability and generalizability of the model, experiments are conducted to analyze the impact of environmental tax rates on results and berthing time on environmental benefits. The results show that optimal solutions can reduce emissions of carbon dioxide, sulfur oxides, nitrous oxides and particulate matters by at least 3.8% while reducing the total cost by 35.9%, compared with the baseline scheme. Meanwhile optimal solutions can reduce emissions by up to 100%, but increase the total cost by 183.7%. Besides, the proposed model has good applicability when the berthing time and environmental tax rates change. In conclusion, the developed method can be widely used for popularizing shore power, promoting port sustainable development, reducing global air pollution and greenhouse gas emissions. Graphical abstract: Image 1 Highlights: Environmental benefits of shore power for ships are calculated. Shore power allocation and berth allocation interact with each other. A cooperative optimization model is proposed for balancing costs and environmental benefits. The proposed model can be widely used to promote port sustainable development.